Malnutrition, illness, poverty, and infant growth: A test of a syndemic hypothesis in Nuñoa, Peru. (February 2022) - Hoke, Morgan K.; McCabe, Kimberly A.
Abstract: The concept of syndemics provides an important framework for understanding the complex interactions of biological and social conditions. Its use in public health and epidemiological research has increased substantially in the past ten years. Many syndemic analyses rely on the use of a sum score and subsequently fail to demonstrate biological interaction, leading some scholars to question the utility of the syndemic approach. Here, we utilize data from 86 mother/infant pairs from the rural district of Nuñoa, Peru to test a potential syndemic relationship among infection, malnutrition and infant growth. Between 2014 and 2015, surveys were conducted to assess household wealth, sanitation, dietary diversity, and reported illness, while anthropometric measures of mothers and infants were conducted to assess nutritional status via height-for-age and weight-for-height z-scores. Ethnographic insight was used in the selection of key economic variables including the development of an agricultural wealth index. We then assessed whether this constellation of health outcomes met the criteria for a syndemic by performing a quantitative analysis in which we tested for (1) an association between economic marginalization and high-risk environments; (2) the concentration of malnutrition, poor growth, and infection; and (3) biological interaction among these health outcomes. We found that economic measures were associated with pathogenic and nutritional risk, and that these in turn were associated with infectious disease, nutritional status, and growth. However, we did not find evidence that the proposed syndemic met criteria (2) or (3). We conclude that, despite being both socially and biologically plausible, a syndemic of malnutrition, poor growth, and infection did not exist in this context. This analysis moves syndemic research forward by demonstrating that such hypotheses are falsifiable, thus presenting a process by which they may be tested and lending support to the use of syndemic theory as an effective analytic framework. Highlights: Economic measures are associated with infectious disease, nutritional status, and growth. No evidence for the concentration of malnutrition, poor growth, and infection. No evidence of biological interactions among malnutrition, poor growth, and infection. We demonstrate the falsifiability of syndemic hypotheses thus showing their utility.